2006
DOI: 10.1037/0022-0167.53.2.214
|View full text |Cite
|
Sign up to set email alerts
|

System for observing family therapy alliances: A tool for research and practice.

Abstract: To advance research and inform practice, the authors developed an observational rating system of client behavior reflecting strong and weak therapeutic alliances in couple and family therapy. The System for Observing Family Therapy Alliances (SOFTA), in both English and Spanish, has 2 dimensions that are common across therapy modalities ("emotional connection to the therapist" and "engagement in the therapeutic process") and 2 dimensions that reflect the uniqueness of conjoint treatment ("safety within the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
149
2
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(168 citation statements)
references
References 27 publications
6
149
2
11
Order By: Relevance
“…Previous studies have indicated that cohesion and agreement within families during family therapy is beneficial with regard to achieving treatment goals [35], [36]. In this study, we did not observe any statistically significant association between concordance between children’s and parents’ reports and reduction of z-BMI.…”
Section: Discussioncontrasting
confidence: 72%
“…Previous studies have indicated that cohesion and agreement within families during family therapy is beneficial with regard to achieving treatment goals [35], [36]. In this study, we did not observe any statistically significant association between concordance between children’s and parents’ reports and reduction of z-BMI.…”
Section: Discussioncontrasting
confidence: 72%
“…Interpreting alliance simply in dyads between each family member and the therapist ignores the complex intrafamilial dynamics that make family therapy unique (Beck et al, 2006;Friedlander et al, 2006). The process of engaging with the therapist aids in developing insights and improvements in parent/youth relationships; increased engagement occurs when the therapist empowers family members to improve their relationships with one another (Bachelor, 1995).…”
Section: Intra-family Alliancementioning
confidence: 96%
“…Two computer-based feedback systems, the Systemic Inventory of Change (STIC; Pinsof et al, 2009) and the System for Observing Family Therapy Alliances (SOFTA; Friedlander et al, 2006) have been developed to serve as both clinical and research tools. Similar systems for tracking therapy outcomes and comparing them with norms have been used to relay clinically relevant information to therapists when their clients are responding poorly to treatment .…”
Section: Threat #3: a Lack Of Feedbackmentioning
confidence: 99%